(untitled) (Research, Society and Development, 2021)
Social participation is a complex phenomenon that needs further studies and critical discussions within the scientific scenario of Mental Health Care for children and adolescents, thus, it is understood that this study contributes to the advancement of knowledge in relation to adolescents with conduct disorder in relation to their social participation. The study aims to verify the main changes in occupational performance with regard to the social participation of adolescents with conduct disorder at a Psychosocial Care Center for Children and Youth in Northeastern Brazil. This is a cross-sectional qualitative study. For its development, a semi-structured questionnaire was used, which is concerned with investigating three major poles of social participation of these adolescents, which would be: the family group, the community and the school. The questionnaire was applied to parents or guardians of adolescents with conduct disorder. The results showed that there was a significant change in occupational performance with regard to the social participation of the participants in this study, demonstrating that health professionals need to understand the importance of social participation in CAPSis with these young people, their families and the community to minimize the suffering of this clientele and their families, favoring social inclusion and reducing society’s prejudice towards these children and adolescents.